A Review of Thermal Design for IGBT Module - Guoyou LIU; Yangang WANG; Haihui LUO; Fang QI; Xiang LI; Yibo WU (Zhongguo dianli)
In this paper, the thermal characteristics and thermal design of IGBT module are reviewed. Firstly, the thermal network model and its dependence on the packaging material’s thermal performance and dimensions are addressed. Then, the thermal design of IGBT module is investigated in terms of semiconductor chip, packaging structure and material. Finally, the main thermal design aspects of conventional IGBT module and new press-pack IGBT module are presented.